Teori Pemberlakuan Hukum Islam di Indonesia - Amir, Nurhikma; Rahman R, Abd.; R, Rahmatiah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article discusses the theory of the application of Islamic law in Indonesia. The research method used is library research, namely by searching and collecting data from libraries such as history books. The results of this research are that there are several theories of the implementation of Islamic law in Indonesia, namely the creed or shahada theory, the receptio in complexu theory (the period of full acceptance of Islamic law), the receptie theory (the period of acceptance of Islamic law by customary law), the exit theory (the theory that requires the theory of receptie no longer applies), the theory of receptie a contrario, and the theory of existence.